Avaliação da Bioatividade de Lignóides na Inibição da Topoisomerase II-a Humana - Bezerra, Amanda de Melo (2011)
The Topoisomerase II is involved in several vital cellular processes such as replication and transcription of DNA, in addition to the segregation of chromosomes. This enzyme catalyzes changes in DNA topology by temporary disruptions and subsequent rearrangement of the double helix and is essential for cell proliferation to occur. Many compounds that interfere with the catalytic activity of this enzyme are effective in chemotherapy of cancer. The development of new inhibitors from plant sources can be a valuable strategy, serving also as a tool for the production of semi-synthetic active agents that do not cause serious damage to the body and with a lower cost. Has already been reported that some lignoids derived from plants have inhibitory action on DNA Topoisomerase II. Plants of the Lauraceae family are sources of bioactive lignoids. Among different species, there are the Licaria aurea and Licaria chrysophylla. In this study, 12 lignoids derived from both species were evaluated for their inhibitory effect on human DNA Topoisomerase II, using etoposide as action control of substances. Two of these compounds showed inhibitory activity against the human enzyme Topoisomerase II. These compounds are the lignan (2S,3S)-Dihydro-dehydrodiconiferyl alcohol-3-(-D-glycopiranosyl)-hexaacetate and the neolignan 1,4-Bis-(3, 4,5-trimethoxyphenyl)-2,3-dimethylbutane.